An in vitro study of dual drug combinations of anti-viral agents, antibiotics, and/or hydroxychloroquine against the SARS-CoV-2 virus isolated from hospitalized patients in Surabaya, Indonesia - Purwati; Miatmoko, Andang; Nasronudin; Hendrianto, Eryk; Karsari, Deya; Dinaryanti, Aristika; Ertanti, Nora; Ihsan, Igo Syaiful; Purnama, Disca Sandyakala; Asmarawati, Tri Pudy; Marfiani, Erika; Yulistiani; et al. (PloS one, 2021)
A potent therapy for the infectious coronavirus disease COVID-19 is urgently required with, at the time of writing, research in this area still ongoing. This study aims to evaluate the in vitro anti-viral activities of combinations of certain commercially available drugs that have recently formed part of COVID-19 therapy. Dual combinatory drugs, namely; Lopinavir-Ritonavir (LOPIRITO)-Clarithromycin (CLA), LOPIRITO-Azithromycin (AZI), LOPIRITO-Doxycycline (DOXY), Hydroxychloroquine (HCQ)-AZI, HCQ-DOXY, Favipiravir (FAVI)-AZI, HCQ-FAVI, and HCQ-LOPIRITO, were prepared. These drugs were mixed at specific ratios and evaluated for their safe use based on the cytotoxicity concentration (CC 50 ) values of human umbilical cord mesenchymal stem cells. The anti-viral efficacy of these combinations in relation to Vero cells infected with SARS-CoV-2 virus isolated from a patient in Universitas Airlangga hospital, Surabaya, Indonesia and evaluated for IC 50 24, 48, and 72 hours after viral inoculation was subsequently determined. Observation of the viral load in qRT-PCR was undertaken, the results of which indicated the absence of high levels of cytotoxicity in any samples and that dual combinatory drugs produced lower cytotoxicity than single drugs. In addition, these combinations demonstrated considerable effectiveness in reducing the copy number of the virus at 48 and 72 hours, while even at 24 hours, post-drug incubation resulted in low IC 50 values. Most combination drugs reduced pro-inflammatory markers, i.e. IL-6 and TNF-α, while increasing the anti-inflammatory response of IL-10. According to these results, the descending order of effective dual combinatory drugs is one of LOPIRITO-AZI>LOPIRITO-DOXY>HCQ-AZI>HCQ-FAVI>LOPIRITO-CLA>HCQ-DOX. It can be suggested that dual combinatory drugs, e.g. LOPIRITO-AZI, can potentially be used in the treatment of COVID-19 infectious diseases.